“You should give a child love and take them warm-heartedly from their parent”: Preschool teachers’ practice and understanding of care - N. C. Phatudi (Perspectives in Education, 2018)
This paper is based on the exploration of township preschool teachers’ perspectives of the act of caring. Caring has always been associated with women as they are seen as nurturers. Their role as mothers is regarded as a natural part of their being. This study explored preschool teachers’ understanding of caring as well as its implementation. Literature confirms that caring has moral nuances and definite emotive features and that the one cared for is likely to develop intellectually. This paper interrogates “caring”, as one of the features of quality. The paper is drawn from a larger qualitative study conducted on teachers’ perspectives on quality. The study was conducted by using photovoice and observation. Caring was highlighted as a key element of quality in the preschools that were studied. Caring was understood within cultural practices of the communities that formed the sites of this study. Data revealed that caring should not be viewed in an exclusionary way that does not take into account the context in which it is practised. It is this caring that has positive spinoffs and has the capability of enhancing the quality of learning.